The Intertextual Game in Ulitskaya’s Novel Medea and Her Children - Kovtun, Natalia (Respectus Philologicus, 2012)
This article attempts to present a reading of Ulitskaya’s novel as a metatext of world culture, as an encrypted message through which the author inveigles “a shrewd reader” into the guessing of discourses (from ancient mythology to works of social realism and postmodernism) in order to detect traces of the initial scenarios proposed to humanity by the Creator. The conceptual basis of the work was the myth of Sophia Wisdom Divine, an artist painting the primary blueprint of the universe and inviting other artists to co-create (the muse and the artist). Ulitskaya’s Sophiology is based on the ideas of the Russian modernists, e.g., Soloviev and Block. The Greek story of Medea—the daughter of King Aeëtes of Colchis and wife of Jason, who headed the expedition of the Argonauts—provides the basic structure of the novel. This myth is one of the most popular in the world among artists. Its interpretive options (from Euripides and Ovid to Anouilh, Pasolini and Petrushevskaya) are evidence for the unity of the text of culture. The novel, then—the ironical statement of the author to enter into the circle of the elect, the family of Medea, whose image is highlighted by signs of Sofia—is the embodiment of style. Medea’s manor is “the navel of the earth” in which the outlines of the Masons are traced; here, time and space, living and dead, sinners and saints converge. The earth itself is read like a book. All the characters are divided into puppets—unable to understand the hidden meaning of the text—and directors/demiurges—artists, musicians, and doctors who write the history of dolls. The typology of female images is constructed on the gender stereotypes of the fin de siècle era: the woman as a sexual object (Gypsy, wanton); femme fatale/vamp (Amazonian, Salomé); and the romantic lover and muse (Madonna, the eternal feminine). The functions of the male characters are associated with Orpheus, Perseus, Pygmalion, and Ulysses, who perform their feats in the name of Beauty. The mission of the reader is to pass the initiation of the plot and guess all its variations with the power of letters resembling dragon’s teeth, to detect in these traces of meaning the “Golden Fleece,” much as Medea who led Jason to such a purpose.